2020
DOI: 10.4103/jehp.jehp_258_18
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the effectiveness of a nutrition education session using flipchart among school-going adolescent girls

Abstract: INTRODUCTION: Adolescence is characterized by a rapid phase of growth and development during which the requirement of nutrition and micronutrients is relatively high. Although there is a decreasing trend in the prevalence of undernutrition among adolescents, the current prevalence of undernutrition is still very high (41.9%). Adolescents with good nutrition knowledge are more likely to follow healthy eating habits. In the light of this, the current study was planned to assess the baseline nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 17 publications
4
8
0
Order By: Relevance
“…BC—Healthy Eating”, which used a multi-component approach with educational, environmental and family elements, a significant increase in the consumption of fresh vegetables and fruits was found [ 16 ]. This finding was confirmed in later studies [ 15 , 17 , 18 , 19 ]. It seems that the success of the program, apart from its complexity, may depend on the complementarity of the program components, as well as the proper identification of health benefits by young people resulting from the adoption of pro-healthy dietary habits [ 20 , 21 ].…”
Section: Introductionsupporting
confidence: 78%
“…BC—Healthy Eating”, which used a multi-component approach with educational, environmental and family elements, a significant increase in the consumption of fresh vegetables and fruits was found [ 16 ]. This finding was confirmed in later studies [ 15 , 17 , 18 , 19 ]. It seems that the success of the program, apart from its complexity, may depend on the complementarity of the program components, as well as the proper identification of health benefits by young people resulting from the adoption of pro-healthy dietary habits [ 20 , 21 ].…”
Section: Introductionsupporting
confidence: 78%
“…A higher proportion of the participants in the intervention group compared to the control group increased their knowledge level of the general signs of anaemia, causes of anaemia, iron-enhancing foods, and iron-inhibiting foods as it showed a statistically significant difference, indicating that nutrition education was effective in enhancing the knowledge level of participants on anaemia and iron. This study adds to the others that showed that nutrition education intervention improves nutrition knowledge level of adolescents [ 32 34 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 56%
“…The findings of this study are consistent with prior studies that suggest that nutrition education in schools can improve knowledge and awareness about anaemia; increase demand and improve compliance with IFA supplements; and change adolescent dietary behaviour. [29][30][31][32][33] The pedagogical approach employed in the education sessions differed from conventional approaches in schools and was designed to be interactive and participatory, which we believe crucially contributed towards greater acceptance of the intervention and a positive impact on knowledge and attitude. 34 Similar studies conducted in school settings in India using varied approaches, such as single or multiple interactive education sessions delivered by doctors, trained experts using flipcharts, videos and other interactive methods have been found to improve knowledge and/or change behaviours related to anaemia and its prevention.…”
Section: Interpretation (In Light Of Other Evidence)mentioning
confidence: 99%
“…34 Similar studies conducted in school settings in India using varied approaches, such as single or multiple interactive education sessions delivered by doctors, trained experts using flipcharts, videos and other interactive methods have been found to improve knowledge and/or change behaviours related to anaemia and its prevention. [29][30][31][32] Evaluation of the Weekly Iron and Folic Acid Supplementation (WIFS) programme in India and other low-and-middle-income countries found that one of the key factors influencing increased uptake of IFA supplements was implementation of a coordinated and timely information education and communication strategy that dispelled misconceptions and rumours, and capitalised on the positive effects. 25,[35][36][37][38][39] Moreover, as indicated by Joe et al (2022), increased awareness and subsequent demand-generation by target groups will help address other institutional barriers related to the supply and distribution of IFA supplements.…”
Section: Interpretation (In Light Of Other Evidence)mentioning
confidence: 99%